Fast method of approximate particular solutions using Chebyshev interpolation. (March 2016) - Lamichhane, A.R.; Young, D.L.; Chen, C.S.
Abstract: The fast method of approximate particular solutions (FMAPS) is based on the global version of the method of approximate particular solutions (MAPS). In this method, given partial differential equations are discretized by the usual MAPS and the determination of the unknown coefficients is accelerated using a fast technique. Numerical results confirm the efficiency of the proposed technique for the PDEs with a large number of computational points in both two and three dimensions.